2019
DOI: 10.1590/2317-1782/20192018225
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas vocais na população pediátrica: Validação da versão brasileira do Questionário de Sintomas Vocais Pediátrico

Abstract: ResumoObjetivo: Validar o Questionário de Sintomas Vocais Pediátrico (QSV-P) para o português brasileiro. Método Aprovado pelo Comitê de Ética (758.309). Participaram desta pesquisa 716 indivíduos, dos quais 367 eram crianças e adolescentes, com e sem alteração vocal, entre 6 e 18 anos, e 349 eram pais/responsáveis, que responderam à versão final do instrumento. Entre os respondentes dessa versão, 272 participaram do teste-reteste, e 32, da sensibilidade. As crianças e os adolescentes entre 6 e 18 anos respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
4
0
5
Order By: Relevance
“…Children are the minority in seeking clinical care, although the prevalence data of childhood dysphonia is up to 38% of the pediatric population (151) . It is believed that pediatric dysphonia has fewer studies by the need for parental consent that do not necessarily want their children as a research subject (151) . The occurrence of studies with children found in this review is in line with the literature (151,196) .…”
Section: Discussionmentioning
confidence: 99%
“…Children are the minority in seeking clinical care, although the prevalence data of childhood dysphonia is up to 38% of the pediatric population (151) . It is believed that pediatric dysphonia has fewer studies by the need for parental consent that do not necessarily want their children as a research subject (151) . The occurrence of studies with children found in this review is in line with the literature (151,196) .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in Brazil, the following protocols are available in the voice clinic practice: Voice-Related Quality of Life (VRQOL) (49) ; Voice Handicap Index (VHI) (56) ; URICA-VOICE Scale (URICA-VOICE) (57) ; Vocal Tract Discomfort Scale (VTDS) (58) ; Voice Activity and Participation Profile (VAPP) (59) ; Vocal Symptom Scale (VoiSS) (60) ; Dysphonia Coping Strategy Protocol (PEED) (61) ; and the Vocal Fatigue Index (VFI) (62) . In addition to others for more specific populations, such as the Modern Singing Handicap Index (MSHI) (63) , Classical Singing Handicap Index (CSHI) (64) , pediatric Voice-Related Quality of Life (pVRQOL) (65) , Transsexual Voice Questionnaire Male to Female (TVQ MtF ) (66) , Screening for Voice Disorders in Older Adults (RAVI) (67) and the Pediatric Vocal Symptoms Questionnaire (PVSQ) (68) , among others.…”
Section: Voice Self-assessment Protocolsmentioning
confidence: 99%
“…The inclusion of the patient's point of view in the assessment is a mandatory part of the vocal clinic routine. There is a huge range of voice self-assessment protocols already validated in Brazil, with different perspectives of analysis components, such as quality of life (49,56,59,65) pathophysiology and presence of symptoms (18,59,62,68) , as well as behavior and cognition (57,61) . The question that always arises for clinicians, especially for beginners, is: "which vocal self-assessment protocol should I use with my patient?"…”
Section: Commentsmentioning
confidence: 99%
“…Atualmente, no Brasil, tem-se disponível na clínica de voz os seguintes protocolos: Qualidade de Vida em Voz (QVV) (49) , Índice de Desvantagem Vocal (IDV) (56) , Escala URICA-VOZ (URICA-VOZ) (57) , Escala de Desconforto de Trato Vocal (EDTV) (58) , Protocolo de Participação e Atividades Vocais (PPAV) (59) , Escala de Sintomas Vocais (ESV) (60) , Protocolo de Estratégias de Enfrentamento das Disfonias (PEED) (61) e Índice de Fadiga Vocal (IFV) (62) . Além de outros para populações mais específicas, como Índice de Desvantagem no Canto Moderno (IDCM) (63) , Índice de Desvantagem no Canto Clássico (IDCC) (64) , Qualidade de Vida em Voz Pediátrico (QVV-P) (65) , Questionário de Autoavaliação Vocal para Transexuais de Homem para Mulher (TVQ MtF ) (66) , Rastreamento de Alterações Vocais em Idosos (RAVI) (67) e Questionário de Sintomas Vocais Pediátrico (QSV-P) (68) , entre outros.…”
Section: Protocolos De Autoavaliação Em Vozunclassified
“…A adição da perspectiva do paciente em sua avaliação faz parte obrigatória da rotina da clínica vocal. Existe uma gama enorme de protocolos de autoavaliação em voz já validados no Brasil, com diferentes perspectivas de eixos de análise, tais como qualidade de vida (49,56,59,65) fisiopatologia e presença de sintomas (18,59,62,68) , além de comportamento e cognição (57,61) . A dúvida que sempre surge aos clínicos, principalmente aos iniciantes é: "qual protocolo de autoavaliação vocal devo utilizar com meu paciente?"…”
Section: Comentáriosunclassified